Aristotle on Microstructures and Capacities. Issue 1 (April 2022) - Popa, Tiberiu
Abstract : A potentially illuminating aspect of Aristotle's study of material properties that has been explored far less systematically and comprehensively than composition is his reliance on structural characteristics that are imperceptibly small, but presumably inferable, if not with certainty, at least with a high degree of confidence. This article is meant to elucidate that aspect and to answer three main questions: (1) What is Aristotle's general explanatory strategy when it comes to the relation between capacities and microstructures? (2) How does he refine certain elements of his explanations, e.g., with respect to specific subtypes of structures and their interaction with the environment? (3) And to what extent could Aristotle's appeal to microstructures be relevant to debates in contemporary metaphysics and philosophy of science?